Pengumpul Harta Dalam Surat Al-Humazah (Tinjauan Semiotika Ferdinand De Saussure) - hikmah, ismi wakhidatul; Yusup, Maulana; Alif, Muhammad Nur (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis paper examines the wealth collector in Surah al-Humazah, where they frequently disregard their obligation to worship God and are continually focused on multiplying their riches until they believe all they acquire could make them eternal. They believe they have abundant wealth, so they easily belittle others. This study employed a literature review method based on Ferdinand de Saussure's semiotic theory approach. The stages of the approach are syntagmatic analysis, paradigmatic analysis, binary opposition, and history confirmation. According to the findings of this study, there is coherence between verses in the Surah al-Humazah when using syntagmatic analysis. Second, wealth collectors are those with immoral tendencies who like to curse and blame. Also, they believe that their fortune would be able to eternalize them, making them hesitant to share. Hence, they threatened with hell huthamah. Furthermore, Surah al-Humazah has a secret message for every Muslim to practice social charity to create harmony among individuals in society.Keywords: al-Humazah; Binary opposition; Paradigmatic; syntagmatic. AbstrakTulisan ini membahas pengumpul harta yang ada dalam surat al-Humazah di mana pengumpul harta sering lalai dengan kewajiban ibadah kepada Tuhan dan selalu terfokus pada cara memperbanyak harta hingga mereka mengira harta yang mereka kumpulkan dapat mengekalkannya, merasa memiliki harta yang banyak sehingga mereka dengan mudahnya merendahkan orang lain. Penelitian ini menggunakan metode studi pustaka dengan pendekatan teori semiotika dari Ferdinand de Saussure dengan langkah yang pertama analisis sintagmatik, kedua analisis paradigmatik, ketiga oposisi biner, keempat mengkonfirmasi sejarah. Hasil dari penelitian ini adalah dengan analisis sintagmatik dalam surat al-Humazah terdapat koherensi antar ayat. Kedua, pengumpul harta ialah mereka yang memiliki sifat amoral yang suka mengumpat dan mencela serta menganggap hartanya dapat mengekalkannya sehingga enggan berinfak akibatnya mereka diancam dengan neraka huthamah. Selain itu surat al-Humazah memiliki pesan tersembunyi, yaitu agar setiap muslim beramal sosial dalam kehidupan bermasyarakat sehingga dalam bermasyarakat terjalin kerukunan antar sesama. Kata Kunci: al-Humazah; Oposisi Biner; Paradigmatik; Sintagmatik.